Determination of Organic Matter by Using Titrimetric and Loss on Ignition Methods for Northern Iraqi Governorates Soils - Maulood, Pakhshan M. (Al-Nahrain Journal of Science, 2022)
The study was carried out to determine soil organic matter content (SOM) using loss on ignition (LOI) and titrant methods. Eighty-four composite soil samples were collected from surface soil of randomly different locations in four governorates of northern parts of Iraq. The percent mean values of SOM recorded were 2.34, 2.399 and 1.821, respectively for Erbil, Sulaymaniyah, Kirkuk, and Duhok soil samples for the LOI method, while lower values were obtained 1.39, 1.595 and 0.98% respectively by using the titrant method for the same soil samples. A low relationship between two SOM procedures was obtained (r2 = 0.462, 0.585 and 0.241) respectively for the same governorates soil samples. Current results revealed that the titrant method is more accurate and convenient to be used for SOM determination of soils in our area, and further studies must be done by using other methods to find the more suitable procedure for this purpose.